The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/rec.12941
|View full text |Cite
|
Sign up to set email alerts
|

Carbon accumulation and vertical accretion in a restored versus historic salt marsh in southern Puget Sound, Washington, United States

Abstract: Few comparisons exist between vertical accretion (VA) and carbon accumulation rates (CARs) in restored versus historic (i.e. reference) marshes. Here, we compare these processes in a formerly diked, sparsely vegetated, restored salt marsh (Six Gill Slough, SG), whose surface is subsided relative to the tidal frame, to an adjacent, relatively pristine, historic salt marsh (Animal Slough, AS). Six sediment cores were collected at both AS and SG approximately 6 years after restoration. Cores were analyzed for bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…At the NRD, previous research has shown that the restoring, subsided, and sparsely vegetated salt marsh (Six Gill Slough, hereafter the Restoring Marsh), accreted sediment at approximately twice the rate of the nearby, historical reference salt marsh (Animal Slough, hereafter the Reference Marsh) since restoration in 2009 (Restoring Marsh: 0.79 ± 0.29 (SD) cm year −1 ; Reference Marsh: 0.41 ± 0.16 cm year −1 ; Drexler et al 2019). In addition, vertical accretion was found to consist of5 5% inorganic matter at the Reference Marsh in contrast to 95% inorganic matter at the Restoring Marsh (Drexler et al 2019). Such data suggest that a greater amount of allochthonous material is being deposited in the Restoring Marsh vs. the Reference Marsh.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…At the NRD, previous research has shown that the restoring, subsided, and sparsely vegetated salt marsh (Six Gill Slough, hereafter the Restoring Marsh), accreted sediment at approximately twice the rate of the nearby, historical reference salt marsh (Animal Slough, hereafter the Reference Marsh) since restoration in 2009 (Restoring Marsh: 0.79 ± 0.29 (SD) cm year −1 ; Reference Marsh: 0.41 ± 0.16 cm year −1 ; Drexler et al 2019). In addition, vertical accretion was found to consist of5 5% inorganic matter at the Reference Marsh in contrast to 95% inorganic matter at the Restoring Marsh (Drexler et al 2019). Such data suggest that a greater amount of allochthonous material is being deposited in the Restoring Marsh vs. the Reference Marsh.…”
Section: Introductionmentioning
confidence: 85%
“…The relative contributions of carbon sources determined by the Bayesian SIMM analysis for the original model were multiplied by the mean carbon accumulation rates at the Reference Marsh and Restoring Marsh to estimate the carbon accumulation rates of individual source components at both sites. Mean carbon accumulation rates in sediments~6 years after restoration at the Restoring Marsh and Reference Marsh were approximately 164 ± 54 and 134 ± 19 g C m −2 year −1 , respectively (Drexler et al 2019).…”
Section: Carbon Accumulation By Sourcementioning
confidence: 93%
See 3 more Smart Citations